Detached Eddy Simulation (DES) of Co-Current Spray Dryer - Noor Intan Shafinas, Muhammad; Jolius, Gimbun (Universiti Malaysia Pahang, 2013)
This paper presents Computational fluid dynamics (CFD) modelling of hydrodynamics in a cocurrent spray dryer. The simulations were performed using two different turbulent models, i.e. standard k-ε (SKE), and the Detached Eddy Simulation (DES). The predicted axial velocity, temperature and humidity profile inside the spray drying chamber were found to be in fair agreement to the experimental data adopted from literature for all turbulence models tested in this work. A great potential of the Detached Eddy Simulation for predicting the flow pattern in a co-current spray dryer was uncovered as its provides more accurate predictions compared to the other models tested in this work.